2018
DOI: 10.1101/272286
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

α-proteobacterial RNA degradosomes assemble liquid-liquid phase separated RNP bodies

Abstract: Ribonucleoprotein (RNP) granules play an important role in organizing eukaryotic mRNA metabolism via liquid-liquid phase separation (LLPS) of mRNA decay factors into membrane-less “droplet” organelles in the cytoplasm. Here we show that the bacterium Caulobacter crescentus Ribonuclease (RNase) E assembles RNP LLPS droplets that we term bacterial RNP-bodies (BR-bodies) similar to eukaryotic P-bodies and stress granules. RNase E requires RNA to assemble a BR-body, and disassembly requires RNA cleavage, suggestin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
172
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(176 citation statements)
references
References 50 publications
4
172
0
Order By: Relevance
“…All in all, along with the few recently discovered cases of bacterial LLPS (Al-Husini et al, 2018;Heinkel et al, 2019;Monterroso et al, 2019), our findings highlight that LLPS is a fundamental, universally exploited mechanism that is governed by similar molecular mechanisms in bacteria and eukaryotes. The LLPS propensity predicted for human SSB homologs hSSB1/SOSB1 and hSSB2/SOSB2 suggests broad evolutionary conservation of this feature (Fig.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…All in all, along with the few recently discovered cases of bacterial LLPS (Al-Husini et al, 2018;Heinkel et al, 2019;Monterroso et al, 2019), our findings highlight that LLPS is a fundamental, universally exploited mechanism that is governed by similar molecular mechanisms in bacteria and eukaryotes. The LLPS propensity predicted for human SSB homologs hSSB1/SOSB1 and hSSB2/SOSB2 suggests broad evolutionary conservation of this feature (Fig.…”
Section: Discussionsupporting
confidence: 60%
“…Whereas LLPS seems to be a heavily exploited process in eukaryotes and viruses (Heinrich et al, 2018;Nikolic et al, 2017Nikolic et al, , 2018Zhou et al, 2019), up until today only a few bacterial proteins were reported to undergo LLPS. These include Caulobacter crescentus Ribonuclease E (RNase E) that orchestrates RNA degradosomes (Al-Husini et al, 2018), Escherichia coli (E. coli) FtsZ that forms the division ring during cell divisions (Monterroso et al, 2019) and Mycobacterium tuberculosis Rv1747 that is a membrane transporter of cell wall biosynthesis intermediates (Heinkel et al, 2019). All in all, the hitherto accumulated observations imply that LLPS is a fundamental mechanism for the effective spatiotemporal organization of cellular space, with emerging but hardly explored functions in bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…5 example, SGs contain multiple conserved helicases, including eIF4A/Tif1 and DDX3/Ded1, in both mammals and yeast, respectively (Jain et al, 2016). Similarly, RNA helicases are found localized in bacterial RNP granules as well (Taghbalout and Rothfield, 2008;Al-Husini et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, recent work suggests that bacteria may indeed contain biomolecular condensates (26). For example, the DEAD-box helicases DeaD, SrmB and RhlE form foci in E. coli (27) and RNase E forms foci in Caulobacter crescentus and other α-proteobacteria (28). Moreover, the disordered C-terminal domain of RNase E is necessary and sufficient for foci assembly in vivo.…”
Section: Introductionmentioning
confidence: 99%